Effects of nine antihypertensive drugs on blood pressure variability in sinoaortic-denervated rats - Wang Jin; Shen Fu-ming; Wang Min-wei; Su Ding-feng (Acta Pharmacologica Sinica, 2016)
Aim: The present work was designed to investigate the effects of nine commonly used antihypertensive drugs on blood pressure (BP) and blood pressure variability (BPV) in conscious sinoaortic-denervated (SAD) rats. Methods: Seventy-two SAD rats were randomly divided into nine groups. They were respectively given nifedipine 3 mg/kg, nitrendipine 5 mg/kg, amlodipine 1 mg/kg, clonidine 10 μg/kg, prazosin 0.5 mg/kg, atenolol 20 mg/kg, telmisartan 20 mg/kg, hydrochlorothiazide 40 mg/kg or captopril 50 mg/kg. The drugs were given via a catheter previously implanted into the stomach. BP was recorded for 5 h from 1 h before drug administration to 4 h after drug administration in conscious, freely moving rats. Results: It was found that all these nine drugs significantly decreased BP in SAD rats. Six of these drugs (nifedipine, nitrendipine, amlodipine, clonidine, prazosin and atenolol) significantly decreased BPV in SAD rats, but the remaining three drugs did not. Clonidine and atenolol increased the heart period and the others did not. No drugs affected the heart period variability. Conclusion: Among nine antihypertensive drugs from different classes, calcium antagonists and sympathetic inhibitors decreased BPV in SAD rats.